Efficacy of yokukansan compared with clonazepam for rapid eye movement sleep behaviour disorder: a preliminary retrospective study. Issue 5 (1st June 2020) - Ozone, Motohiro; Shimazaki, Hayato; Ichikawa, Hikaru; Shigeta, Masahiro
Abstract: Aim: Rapid eye movement sleep behaviour disorder (RBD) is characterized by abnormal behaviours accordant with nightmares during rapid eye movement sleep and is considered a prodromal marker of dementia with Lewy body. Most common in the elderly population, RBD is generally treated with clonazepam (CZP), a long‐term acting benzodiazepine antiepileptic. As such, alternative drugs for RBD are urgently needed to minimize the adverse effects peculiar to benzodiazepines. The efficacy of yokukansan (YKS), a traditional Japanese herbal medicine, on RBD was initially reported by Shinno et al. in 2008. However, no study has compared YKS with CZP. Therefore, this study aimed to clarify the possibility of using YKS as an alternative to CZP. Methods: This was a retrospective cohort study conducted at Jikei University Affiliated Hospital. The subjects were selected from 36 outpatients who had been diagnosed with RBD based on the International Classification of Sleep Disorders, third edition. Of the 23 who met the inclusion criteria but not the exclusion criteria, 11 were treated with YKS monotherapy, and 12 were treated with CZP monotherapy. The primary outcome was the total score on the Japanese version of the Rapid Eye Movement Sleep Behaviour Disorder Questionnaire (RBDQ‐JP), and the secondary outcomes were the scores from the eight‐item Short‐Form Health Survey and factors 1 and 2 of the RBDQ‐JP. Results: The mean total RBDQ‐JP score significantly improved from 52.5 to 21.7 ( P = 0.002) after treatment with YKS (mean dosage: 3.0 g/day), which was similar to the change after CZP treatment (from 43.8 to 21.3). On RBDQ‐JP factor 1 (dream content), the mean score on five of six items significantly improved after treatment with YKS. There was no significant change in Short‐Form Health Survey scores after treatment with either drug. Potassium concentrations were within the normal range in patients treated with YKS. Conclusions: The present results suggest that a small amount of YKS may be an alternative to CZP for RBD, without remarkable adverse events. Further study is needed to prospectively clarify the efficacy and safety of YKS in more detail.